Methods to asses mental rotation and motor imagery - Dietz, M.; Wiemeyer, J. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
Spatial abilities are the basic precondition to process visual-spatial information no matter whether that information derives from a digital or a real source. They play an important role in many different areas of life. Vocation, leisure, education and sport are affected by perceptional abilities. However, in sport science this field of research is quite underestimated. Mental rotation tasks occur for example during the early phase of motor learning processes when a motor imagery as an internal representation develops to govern the imitation of the presented model. While IT-based applications are applied to support the imagery process, their actual impact on learning may depend on the level of spatial abilities. To study the relations between spatial abilities and the development of a proper motor imagery two different test instruments, MRT BIO (Mental Rotation Test for biological objects) and PiCaST (Picture Card Selection Test), were developed. Those testing tools and the associated research options are presented in the current paper.